Exploring Ideological Positioning in Barack Obama’s Speech on Same-Sex Marriage: An Appraisal Theory Analysis - Jabbar Kadhim, Adawiya; Abdulhameed Faris, Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The current qualitative and descriptive study examines the stance of one of America’s critical figures, President Barack Obama, on the sensitive phenomenon of same-sex marriage by utilizing Appraisal Theory. The study aims to analyze a series of Obama’s discourses from 2004 to 2011, thus it helps the reader grasp how well-known the American political figure like Obama uses language to influence the public and policies regarding LGBTQ+ rights. The findings show a remarkable shift in Obama’s rhetoric, evolving from a cautious endorsement of civil union to a strong advocacy for marriage equality. Utilizing the Appraisal theory helps deconstruct Obama’s use of language to transfer emotions, judgment, and engagement. Obama tries to show the audience his fairness, empathy, and inclusivity. His ability to engage with diverse perspectives and intensify his advocacy efforts reflects his growing commitment to social justice. The study illustrates the powerful role of political discourse in fostering social change, challenging discrimination, and promoting equality